THE ADVENTURE OF THE RADICAL ISLAMIC GROUP MEMBERS OF THE FREE ACEH MOVEMENT IN SEUMPAMA MATAHARI NOVEL: Study of Genetic-Structuralism (JOURNAL OF INDONESIAN ISLAM, 2018)
Literary work is a product of social class which is used to express the worldview. The social class action or idea described in literary work is the interpretation of the author. This study investigated the work of Arafat Nur Seumpama Matahari which is from the journal of a former combatant of the Free Aceh Movement named Thayeb Loh Angen. The objective of the study was to capture the moderate Islamic social class ideas or aspirations using Lucien Goldmann’s theory of genetic-structuralism. The results showed that the author represents an averageIslamic social class to express the worldview of nationalist-humanist and humanist-religious. In other words, moderate Islamic social level or non-violent Islam did not agree with the emergence of radical Islamic social groups in Indonesia. It is because the militant Islamic social groups contradicted to the concept of Nawa Cita as stated in the national principle of the Republic of Indonesia, Pancasila. Therefore, the combatants of the Free Aceh Movement should give up their idea to form the Indonesian Islamic State and join the Republic of Indonesia.